Comparison of fermented fruit juice as a carrier for isolation phosphate-solubilizing bacteria from rice root (Journal of Tropical Resources and Sustainable Science (JTRSS), 2022)
Fermented fruit juice is the material use to increase the soil microbial activity as it made up from fermented fruit in the container for a several time before it became a liquid compose fertilizer. It contains a lot of substances such as an organic compound which is one of the important nutrient source for bacteria in soil. By applying the fermented fruit juice (FFJ) in soil, it will help to increase the soil fertility itself. The aim of the present study is investigate the targeted soil bacteria which is phosphate-solubilizing bacteria inside the soil paddy root. This study was also revealed type of fruit that been used for fermented fruit juice namely corn cobs, coconut, and fruit waste. The statistical analysis has been conducted by using IBM SPSS version 2.0 for the bacteria population calculation. The findings of the present study showed there is significant different between the bacteria population among the treatments and fermented fruit juice can be used as carrier for phosphate solubilizing bacteria and one of the effective biofertilizer to increase soil fertility.
Keywords: phosphate-solubilizing bacteria; bacteria population; fermented fruit juice; rice; soil microbes